MOOSE EXPERIMENTALLY INFECTED WITH GIANT LIVER FLUKE (FASCIOLOIDES MAGNA) - Lankester, Murray W.; Foreyt, William J. (Lakehead University, 2011)
Moose (Alces alces) are abnormal, dead-end hosts of the giant liver fluke Fascioloides magna. The worms migrate extensively in moose causing considerable hepatic tissue damage before eventually dying. Few reach sexual maturity and eggs are seldom, if ever, passed in feces. Occurrence of the parasite in moose depends on the presence of a competent definitive host and suitable aquatic snail intermediate hosts of the genus Lymnaea. There is no clinical evidence that F. magna kills moose although the considerable tissue pathology seen in some heavily infected livers is suggestive that they do. In this study, 2 farm-reared calves (2 months old) and a yearling moose (15 months old) were given 50, 110, and 225 F. magna metacercariae, respectively, and observed for 12.5-16 months. No outward signs of disease were observed. The livers of the 2 animals infected as calves were swollen and contained bloody tracks, extensive fibrosis, and capsules; 1 and 11 immature flukes were recovered. The liver of the animal infected as a yearling had 3 large, thick-walled capsules but no flukes. Weight gain and behaviour of all were similar to those of uninfected farm-reared moose. Known aspects of the biology of this parasite and our experimental results suggest that F. magna is unlikely to have been a major factor in the recent moose decline in northwestern Minnesota.